The early psychological impact of the covid-19 pandemic among young swimmers during home confinement) - KARAGÖZOĞLU, CENGİZ (My University, 2021)
Background: During the ongoing COVID-19 outbreak, few studies have focused on sport samples. The aim of the study was to investigate the early psychological impacts of the COVID-19 outbreak among young swimmers. Subjects and methods: The sample comprised 429 swimmers (229 boys, 200 girls, mean age 13.88 IURP7XUNH\, with a mean competitive sport experience of 5.22 years. A personal information form was administered to collect data regarding demographics, sport-related experience, and home confinement effects, along with the Beck Anxiety Inventory (BAI). Results: During the first 30 days of home confinement, WKH VZLPPHUV¶ general BAI scores were low, with only 10 percent showing moderate or severe anxiety levels. Girl swimmers had significantly higher anxiety levels than boys. Girl swimmers also reported positive and negative change in their relationship with their parents and expected closer help from their parents. The 14-15 year age group had significantly higher anxiety levels than the other age groups. The lack of pool training was associated with the VZLPPHUV¶DQ[LHW\ Conclusions: Improving athlete-parent interaction and providing coping programs for adolescent athletes may help to reduce anxiety and other negative effects of home confinement during COVID-19.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Beden Eğitimi ve Spor; Diğer; Social Sciences and Humanities; Education; Physical Education and Sports; Other; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; EĞİTİM, BİLİMSEL DİSİPLİNLER; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; EDUCATION, SCIENTIFIC DISCIPLINES; Social Sciences & Humanities